Study Reinforcing and Applied Load of Wear Rate for Epoxy Composites - Abdullah, Mustafa Z.; Ahmed, Oday H.; Maki, Sameer A.; Hessian, Abdurrahman M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This research studies Reinforcing and applied load of  Wear Rate for Epoxy composites contains from epoxy resin (Ep) as a matrix material and reinforced by Gawain red wood flour , Russian white wood flour , glass powder and rock wool fibers , with volume fraction (20%) for all samples in lab conditions.  by using the load (10,20 ,30 ,40) Newton of iron disc for testing  time(10) minute, and the results have shown that the reinforcing of epoxy resin led to decrease  wear rate for all samples except the hybrid composites reinforced earth glass powder , that the wear rate values  decrease  from   (22Ã—10-9g/cm) to (4Ã—10-9g/cm) of composite material(Ep+R.W.F) and thus(Ep+W.W.F)   at last(Ep+R.W+R.W.F+W.W.F)  , but the  applied load increase led to increose wear rate for all samples  .